2019
DOI: 10.3389/fnins.2019.00998
|View full text |Cite
|
Sign up to set email alerts
|

A Neuromorphic Digital Circuit for Neuronal Information Encoding Using Astrocytic Calcium Oscillations

Abstract: Neurophysiological observations are clarifying how astrocytes can actively participate in information processing and how they can encode information through frequency and amplitude modulation of intracellular Ca2+ signals. Consequently, hardware realization of astrocytes is important for developing the next generation of bio-inspired computing systems. In this paper, astrocytic calcium oscillations and neuronal firing dynamics are presented by De Pittà and IF (Integrated & Fire) models, respectively. Consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The hardware analysis of the proposed astrocyte model in desynchronizing the hypersynchronous coupled neurons and regulating the synaptic transmission between presynaptic and postsynaptic neurons has the same performance of the original model. The comparison results of the hardware realization in terms of the number of resources and maximum speed have been performed between the modified models and the previous proposed tripartite synapse models in [17], [27], [43], [50]- [52]. These results are reported in Table . IV.…”
Section: Implementation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hardware analysis of the proposed astrocyte model in desynchronizing the hypersynchronous coupled neurons and regulating the synaptic transmission between presynaptic and postsynaptic neurons has the same performance of the original model. The comparison results of the hardware realization in terms of the number of resources and maximum speed have been performed between the modified models and the previous proposed tripartite synapse models in [17], [27], [43], [50]- [52]. These results are reported in Table . IV.…”
Section: Implementation Resultsmentioning
confidence: 99%
“…Furthermore, the frequency of the design in [51] is reported 139MHz. A neuromorphic digital design for neuroglial interaction model by employing the linear approximation method is realized in [52]. Based on their research work, 5 multipliers are reported in the high-level utilization table.…”
Section: Implementation Resultsmentioning
confidence: 99%
“…Recently, there has been extensive literature reporting astrocyte computational models and their impact on synaptic learning (De Pittà et al, 2012 ; Manninen et al, 2018 ). Continuing these fundamental investigations to decode neuro-glia interaction, there have been recent neuromorphic implementations of astrocyte functionality in analog and digital Complementary Metal Oxide Semiconductor (CMOS) hardware (Möller et al, 2007 ; Irizarry-Valle and Parker, 2015 ; Naeem et al, 2015 ; Ranjbar and Amiri, 2017 ; Karimi et al, 2018 ; Faramarzi et al, 2019 ). For instance, analog CMOS circuits capturing the neural-glial transmitter behavior have been demonstrated (Joshi et al, 2011 ; Irizarry-Valle et al, 2013 ; Irizarry-Valle and Parker, 2015 ; Lee and Parker, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, analog CMOS circuits capturing the neural-glial transmitter behavior have been demonstrated (Joshi et al, 2011 ; Irizarry-Valle et al, 2013 ; Irizarry-Valle and Parker, 2015 ; Lee and Parker, 2016 ). There is also increasing interest in low-complexity FPGA implementation of the astrocyte computation models (Nazari et al, 2015 ; Ranjbar and Amiri, 2016 , 2017 ; Karimi et al, 2018 ; Faramarzi et al, 2019 ). However, the primary focus has been on a brain-emulation perspective, i.e., implementing astrocyte computational models with high degree of detail in the underlying hardware.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been extensive literature reporting astrocyte computational models and their impact on synaptic learning [8,9]. Continuing these fundamental investigations to decode neuro-glia interaction, there have been recent neuromorphic implementations of astrocyte functionality in analog and digital Complementary Metal Oxide Semiconductor (CMOS) hardware [3,[10][11][12][13][14]. While there has been extensive work on exploring post-CMOS technologies for mimicking bio-realistic computations due to the prospects of low-power and compact hardware design, they have been only studied from standalone neuron/synapse perspective.…”
Section: Introductionmentioning
confidence: 99%